A real-business-cycle model with reciprocity in labor relations and a government sector - Aleksandar Vasilev (Economics and Econometrics Research Institute (EERI), 2017)
In this paper we introduce reciprocity in labor relations and government sector to in- vestigate how well the real wage rigidity that results out of that arrangement explains business cycle fluctuations in Bulgaria. The reciprocity mechanism described in this paper follows Danthine and Kurmann (2010) and is generally consistent with micro- studies, e.g. Lozev, Vladova, and Paskaleva (2011) and Paskaleva (2016). Rent-sharing considerations, and worker's own past wages turn out to be the most important as- pects of how labor contracting happens. In contrast, aggregate economic conditions, as captured by the employment rate, are not found to be quantitatively important for wage dynamics. Overall, the model with reciprocity and fiscal policy performs well vis-a-vis data, especially along the labor market dimension.
Keywords: E24; E32; J41; 330; General equilibrium; reciprocity; gift exchange; efficiency wages; unemployment; fiscal policy; Bulgaria